2023
DOI: 10.3390/s23031297
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Objective Image Quality Metrics Range Guaranteeing Visually Lossless Compression

Abstract: The usage of media such as images and videos has been extensively increased in recent years. It has become impractical to store images and videos acquired by camera sensors in their raw form due to their huge storage size. Generally, image data is compressed with a compression algorithm and then stored or transmitted to another platform. Thus, image compression helps to reduce the storage size and transmission cost of the images and videos. However, image compression might cause visual artifacts, depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The first factor is a used coder and the peculiarities of distortions introduced by it. As known, JPEG introduces blocking effects (artifacts) (Slone et al, 2000;Afnan et al, 2023) and this is undesired [similar effects, but to a lesser degree, can be observed for other coders based on discrete cosine transform (DCT) (Ponomarenko et al, 2005); because of this, image deblocking is often used after decompression]. In turn, wavelet-based coders such as, e.g., JPEG 2000 (Christopoulos et al, 2000) and SPIHT (Kim and Pearlman, 1997) produce ringing artifacts (Punchihewa et al, 2005;Kim et al, 2010;Zhang et al, 2012) and this is undesired as well.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The first factor is a used coder and the peculiarities of distortions introduced by it. As known, JPEG introduces blocking effects (artifacts) (Slone et al, 2000;Afnan et al, 2023) and this is undesired [similar effects, but to a lesser degree, can be observed for other coders based on discrete cosine transform (DCT) (Ponomarenko et al, 2005); because of this, image deblocking is often used after decompression]. In turn, wavelet-based coders such as, e.g., JPEG 2000 (Christopoulos et al, 2000) and SPIHT (Kim and Pearlman, 1997) produce ringing artifacts (Punchihewa et al, 2005;Kim et al, 2010;Zhang et al, 2012) and this is undesired as well.…”
Section: Introductionmentioning
confidence: 93%
“…Noise type and its spatial-spectral properties are taken into consideration in (Lastri et al, 2005;Ponomarenko et al, 2011) to provide invisibility of distortions. Correlation between image quality metrics and distortion visibility threshold has been studied (Kim et al, 2010;Wolski et al, 2018;Afnan et al, 2023). It has been shown that visual quality metrics, both widely known and the ones designed recently (Johnson et al, 2011;Wolski et al, 2018;Afnan et al, 2023) perform better than conventional peak signal-to-noise ratio (PSNR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retina quality assessment approaches are of two types: Objective methods whose aim is to investigate the presence of some specific features which must be present for compliance to some standards and subjective methods where the quality of an image is done subjectively by an expert thus classifying the image as either of poor quality or of quality [10]. For subjective method, judgement on quality is done as per the point of view of an expert without an explanation on why an image has been classified as of quality or not, meaning it can be classified as of non-quality by another expert, so quality takes different meanings for different experts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Te compression evaluation index is an essential basis for evaluating the compression efect of the algorithm [38]. In this paper, the performance of the algorithm is investigated using fve metrics: trajectory similarity (TS), trajectory compression rate (CR), length loss rate (LLR), algorithm running time, and algorithm overall efciency (AOE).…”
Section: Compression Evaluation Indicatorsmentioning
confidence: 99%